African Human Rights Yearbook / Annuaire africain des droits de l'homme (Pretoria University Law Press (PULP), 2018)
The three institutions making up the African regional human rights system, the African Court on Human and Peoples' Rights, the African Commission on Human and Peoples' Rights, and the African Committee of Experts on the Rights and Welfare of the Child, decided to jointly publish the African Human Rights Yearbook, to spearhead studies on the promotion and protection of human rights, and to provide a forum for constructive engagement about the African human rights system with academics and other human rights commentators on the continent. Volume 2 of the Yearbook, published in 2018, contains 21 contributions by scholars from Africa and beyond. Les trois institutions qui composent le système régional africain des droits de l'homme, la Cour africaine des droits de l'homme et des peuples, la Commission africaine des droits de l'homme et des peuples et le Comité africain d'experts sur les droits et le bien-être de l'enfant ont décidé de publier conjointement l'Annuaire africain des droits de l'homme pour encourager les études sur la promotion et la protection des droits de l'homme et offrir un forum d'interaction constructive sur le système avec les universitaires et observateurs du continent. Le Volume 2 de l'Annuaire, publié en 2018, contient 21 contributions de chercheurs du continent et d'ailleurs.